Дослідження перехідних процесів при керованому включенні енергетичних об’єктів - Слоньова, Лариса Вікторівна (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Трансформація енергетичного сектору України – інтеграція до європейських енергосистем, реалізація «зеленого курсу», розвиток відновлюваної генерації та децентралізованих ресурсів – створюють нові технічні виклики: збільшення частки генерації із нелінійною поведінкою, необхідність швидких включень та відключень, широке застосування електроніки та перетворювачів, нестандартні режими провідності. У таких умовах перехідні процеси при керованому включенні можуть призводити до значної перенапруги, коливань струмів, реактивних чи гармонічних навантажень, порушення стійкості, що підвищує потребу в глибинному дослідженні їх параметрів, методики моделювання, заходів пом’якшення та управління.

The transformation of Ukraine's energy sector – integration into European energy systems, implementation of the "green course", development of renewable generation and decentralized resources – creates new technical challenges: an increase in the share of generation with nonlinear behavior, the need for fast switching on and off, widespread use of electronics and converters, non-standard conduction modes. Under such conditions, transients during controlled switching can lead to significant overvoltage, current fluctuations, reactive or harmonic loads, and stability disturbances, which increases the need for in-depth study of their parameters, modeling techniques, mitigation measures, and control The transformation of Ukraine's energy sector – integration into European energy systems, implementation of the "green course", development of renewable generation and decentralized resources – creates new technical challenges: an increase in the share of generation with nonlinear behavior, the need for fast switching on and off, widespread use of electronics and converters, non-standard conduction modes. Under such conditions, transients during controlled switching can lead to significant overvoltage, current fluctuations, reactive or harmonic loads, and stability disturbances, which increases the need for in-depth study of their parameters, modeling techniques, mitigation measures, and control
Study of transient processes during controlled switching on of energy facilities
Керівник роботи: Пантєлєєва Ірина Вікторівна, кандидат технічних наук, доцент, доцент кафедри електротехніки та електроенергетики
Keywords: TECHNOLOGY::Electrical engineering, electronics and photonics::Electric power engineering; перехідний процес; кероване включення; силовий трансформатор; конденсаторна батарея; високовольтний вимикач; стійкість системи; transient process; controlled switching; power transformer; capacitor bank; high-voltage switch; system stability